Single Procedure Saline Lavage for Treatment of Inspissated Bile - Nafisa Sideeka; Raja Shaikh; Gulraiz Chaudry (Case Reports in Radiology)
Inspissated bile syndrome is a rare cause of cholestatic jaundice in infancy, occurring due to obstruction of the biliary ducts and gallbladder by biliary sludge. Traditional methods of treatment include surgical drainage or cholecystostomy drain placement. Both can be associated with complications and prolonged admission. We present 2 cases treated with a single percutaneous needle puncture of the gallbladder followed by saline lavage. Two neonates presented with cholestatic jaundice and sonographic evidence of biliary sludge and dilation of the common bile duct. Single sonographic-guided needle puncture of the gallbladder was followed by irrigation with saline. Clearing of the biliary sludge was confirmed by sonography and cholecystocholangiography. There was resolution of the cholestatic jaundice, with no complications or repeat procedures.